Counter electrodes from platinum alloy nanotube arrays with ZnO nanorod templates for dye-sensitized solar cells. (1st February 2016) - Yang, Qiming; Duan, Jialong; Yang, Peizhi; Tang, Qunwei
Graphical abstract: Highlights: PtAg and PtPd alloy NTs are synthesized using ZnO nanorod templates. The ZnO templates can be dissolved during the growth of alloy NTs. The bimetallic PtM alloy NTs are employed as CE electrocatalysts of DSSCs. The DSSCs yield efficiencies of 8.09% and 7.34% for PtPd and PtAg, respectively. Abstract: Exploration of efficient platinum alloy counter electrodes (CEs) and understanding their electrocatalytic mechanism toward I3 − reduction reaction have been two arising objectives for high-efficiency dye-sensitized solar cells (DSSCs). Here we demonstrate the experimental realization of bimetallic PtM (M = Pd, Ag) alloy nanotube (NT) CE electrocatalysts by an one-step templated synthesis for efficient DSSCs. The preliminary results demonstrate that the alloying of Pt with Pd or Ag for high surface-to-volume CE can significantly enhance the electrocatalytic activity in comparison with pristine Pt electrode. The promising electrocatalytic performances of the PtM CEs are mainly attributed to the good matching of their work functions to redox potential of I − /I3 − couples and electron-enriched alloy surface. When fabricated into liquid-junction DSSCs, the impressive power conversion efficiencies up to 8.09% and 7.34% are determined for the cells with PtPd and PtAg NTs, yielding cell efficiencies enhancements of 18.4% and 5.9% in comparison with 6.93% for pristine Pt based DSSC, respectively. Moreover, the long-term stabilities are also increased due to competitive reactions between Pd/Ag and liquid electrolyte, protecting the Pt atoms from being dissolved by redox electrolyte.